Determination of aflatoxin existence in mixed feed, wheat flour and bulgur samples - Halis Oğuz; Ferhan Nizamlıoğlu; İffet Dinç; Kamil Üney; Hasan Aydın (Eurasian Journal of Veterinary Sciences)
Aim: The main goal of this study was to determine the aflatoxin (AF) contamination in mixed feed, wheat flour and bulgur samples collected from Konya, Karaman and Mersin provinces. Materials and Methods: A total of 570 samples including 150 mixed feed, 210 wheat flour and 210 bulgur samples were collected from Konya, Karaman and Mersin provinces from May 2005 to August 2006 in different seasons. The samples were analyzed by Thin Layer Chromatography-Scanner methods. Results: None of wheat flour and bulgur samples were found to be positive for AF contamination. Three mixed feed samples collected from Konya region were found 1 ppb and one sample from Mersin province was found 0.5 ppb AFB1 contamination. These AF levels determined in mixed feed were found to be below from the maximum permissible level determined by Ministry of Agriculture and Rural Affairs ofTurkey. Conclusion: In this study, the results of analyses in the feed, wheat flour and bulgur samples were evaluated as a satisfying result for public health and animal production. Preventive measures are very important before contamination of feeds and foods by AF. There is need for continued awareness campaigns among consumers, producers and export-importers on the risks associated with exposure to AF. Continuous surveillance program may be warranted to monitor regularly the occurrence of AF in sensitive foods and foodstuffs which consumed by human.